Fluid Shear Stress Increases the Intra-cellular Storage Pool of Tissue-type Plasminogen Activator in Intact Human Conduit Vessels - Sjögren, Lena Selin; Gan, Liming; Doroudi, Roya; Jern, Christina; Jungersten, Lennart; Jern, Sverker (Thrombosis and Haemostasis, 2000)
We investigated the effect of shear stress on the expression of tissuetype plasminogen activator (t-PA) in intact human conduit vessels. Human umbilical veins were exposed to high or low shear stress (25 vs < 4 dyn/cm2) at identical intraluminal pressure (20 mmHg) for 1.5, 3, and 6 h in a new computerized biomechanical perfusion system. High shear perfusion induced a marked, time-dependent increase in t-PA immunostaining in both the endothelium and the media. t-PA relative to GAPDH gene expression increased by 54 ± 14% in highcompared to low-sheared vessels (p = 0.002). By contrast, t-PA release into the perfusion medium was similar in vessels perfused under high or low shear stress conditions. The results show that shear stress independently of pressure is a potent fluid mechanical stimulus for upregulation of the intracellular storage pool of t-PA in the vascular wall of fresh human conduit vessels. The shear effect is associated with an increased t-PA gene expression.
Keywords: t-PA; shear stress; endothelium; immunohistochemistry; gene expression